2021
DOI: 10.9734/ibrr/2021/v12i130141
|View full text |Cite
|
Sign up to set email alerts
|

Haematological Study on the Effects of Goko Cleanser (Herbal Mixture) on Adult Female Wistar Rats

Abstract: Introduction: Goko cleanser is one of the popular herbal mixtures used by the Nigerian populace. This study was carried out to evaluate the effects of this herbal mixture on some haematological parameters of adult female Wistar rats. Methodology: A total of twenty five Wistar rats weighing about 160 – 280g were divided into five groups according to their corresponding weights. The groups were designated as groups 1 – 5. Group 1 served as the control group, while groups 2, 3, 4, and 5 received 1000mg/Kg, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…This may be attributed to the phytochemical constituents of the plant composition of the Dr Iguedo Goko Cleanser®. For instance, Onyejike et al [ 19 ] reported that the herbal mixture contains tannins, saponins and flavonoids, and these plant chemicals are known to impact spermatogenesis. A typical example is tannins extracted from Z. officinale (a plant composition of the product) which have been reported to increase sperm parameters [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…This may be attributed to the phytochemical constituents of the plant composition of the Dr Iguedo Goko Cleanser®. For instance, Onyejike et al [ 19 ] reported that the herbal mixture contains tannins, saponins and flavonoids, and these plant chemicals are known to impact spermatogenesis. A typical example is tannins extracted from Z. officinale (a plant composition of the product) which have been reported to increase sperm parameters [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Study of the hematological variables like haemeglobin (Hb) concentration, Pack Cell Volume (PCV), Red Blood Cell (RBC) and White Blood Cell (WBC) count proffer useful information about the haematological toxicities [61]. Yagari at the dose levels of 250 and 500 mg/kg b.w produced no significant changes in the hematological parameters.…”
Section: Discussionmentioning
confidence: 99%